Application Of Scaffolding Method in Improving Learning Outcomes on The Material Of Respecting Parents at Elementary School 101943 Bengkel - Susanti, Eva; Murianto; Saragih, Desi Asmaini; Lubis, Affridha Yani; Rahimah (Jurnal Cendekia Islam Indonesia, 2025)
his study aims to analyze the effectiveness of the scaffolding method in improving student learning outcomes on the material of respecting parents at SDN 101943 Bengkel, Perbaungan District. Scaffolding is a learning strategy that provides gradual guidance to students until they can understand the material independently. In this study, the method used was classroom action research (CAR) with a quantitative approach. Data were collected through observation, learning outcome tests, and interviews to assess the development of student understanding before and after the implementation of scaffolding. The results showed that the scaffolding method contributed positively to improving students' understanding of the material of respecting parents. The support provided by the teacher, such as guiding questions, concrete examples, and group discussions, helped students build better understanding. In addition, students became more active in the learning process and were able to internalize the moral values ​​taught. In conclusion, the systematic and sustainable application of the scaffolding method can improve student learning outcomes, especially in material related to moral values. Therefore, this method can be an effective learning alternative at the elementary school level.